Two cases of carfilzomib-induced thrombotic microangiopathy successfully treated with Eculizumab in multiple myeloma - Rassner, Michael; Waesch, Ralph; Schiffer, Mario; Schneider, Johanna; Mackensen, Andreas; Engelhardt, Monika; Baur, Rebecca (BMC Nephrology, 2021)
Background Treatment with proteasome inhibitors like carfilzomib in patients with multiple myeloma (MM) can induce thrombotic microangiopathy (TMA) characterized by neurological symptoms, acute kidney injury, hemolysis and thrombocytopenia. Successful treatment with the monoclonal antibody eculizumab was described for these patients, but reports of ideal management and definitive treatment protocols are lacking. Case Presentation The first case describes a 43-years-old IgG-kappa-MM patient that developed TMA during the first course of carfilzomib-lenalidomide-dexamethasone (KRd) consolidation after autologous stem cell transplantation (ASCT). In the second case, a 59-years-old IgG-kappa-MM patient showed late-onset TMA during the fourth and last cycle of elotuzumab-KRd consolidation within the DSMM XVII study of the German study group MM (DSMM; clinicalTrials.gov Identifier: NCT03948035). Concurrently, he suffered from influenza A/B infection. Both patients had a high TMA-index for a poor prognosis of TMA. Therapeutically, in both patients plasma exchange (TPE) was initiated as soon as TMA was diagnosed. In patient #1, dialysis became necessary. For both patients, only when the complement inhibitor eculizumab was administered, kidney function and blood values impressively improved. Conclusion In this small case series, two patients with MM developed TMA due to carfilzomib treatment (CFZ-TMA), the second patient as a late-onset form. Even though TMA could have been elicited by influenza in the second patient and occurred after ASCT in both patients, with cases of TMA post-transplantation in MM being described, a relation of TMA and carfilzomib treatment was most likely. In both patients, treatment with eculizumab over two months efficiently treated TMA without recurrence and with both patients remaining responsive months after TMA onset. Taken together, we describe two cases of TMA in MM patients on carfilzomib-combination treatment, showing similar courses of this severe adverse reaction, with good responses to two months of eculizumab treatment.
CRIS-Team WoS Importer:2021-02-12